Hubungan Antara Praktik Ekonomi, Lingkungan, Sosial, dan Tata Kelola dengan Nilai Perusahaan Efek Mediasi Kinerja Keuangan - Meiliza Nuraini; Mukhlis; Shelly Febriana Kartasari (SAFE-Network, 2023)
The purpose of this study was to examine the effect of economic, environmental, social and governance performance on companies with financial performance as a mediating variable. This study took a sample of 10 companies on the Indonesia Stock Exchange, which were published in financial reports from 2017-2022. This research analysis method using path analysis. The results of the study show that economic performance, environmental performance, social performance and governance performance have no effect on firm value. Financial performance has no effect on company value both before Covid-19 and after Covid-19. Before Covid-19 economic performance had an effect on company value, but after Covid-19 economic performance had no effect on company value. Before and after Covid-19 environmental performance did not affect company value Before Covid-19 social performance had an effect on company value, but after Covid-19 social performance had no effect on company value. Before and after Covid-19, governance performance did not affect company value. Economic performance, environmental performance, social performance, and governance performance did not directly affect company value through financial performance, both before Covid-19 and after Covid-19.